matematicas

como factorizar (x^3+2x^2-5x-6)/(x^3-7x+6)

  1. 👍 40
  2. 👎 25
  3. 👁 365
  1. http://en.wikipedia.org/wiki/Rational_root_theorem

    http://es.wikipedia.org/wiki/Teorema_de_la_raíz_racional

    You find that

    x = -1, x = 2 and x = -3 are roots of x^3+2x^2-5x-6, therefore:

    x^3+2x^2-5x-6 = (x+1)(x-2)(x+3)

    x = 1, x = 2 and x=-3 are roots of x^3-7x+6, therefore:

    x^3-7x+6 = (x-1)(x-2)(x+3)

    1. 👍 0
    2. 👎 0
  2. how would you do it without synthetic div. can you factor it like a quadratic

    1. 👍 0
    2. 👎 0

Responde esta Pregunta

Primer Nombre

Tu Respuesta